WORK FROM HOME IN ORGANIZATIONS: LITERATURE REVIEW - Febriani, Andika Wulan; Sopiah, Sopiah (International Journal of Multidisciplinary Research and Literature, 2022)
This literature review focuses on the entire world. Researchers find that working from home increases productivity for roughly two-thirds of employees by making better use of time and travel and meet higher performance standards. The article investigates working from home on employee productivity, focusing on organizations that boost employee productivity. This study examined 30 reports to determine the organizational factor's impact when working from home. Today, working from home is a famous work arrangement with companies and employees using it to perform flexible and automated work. This study examines the impact of employees working from home (Vyas & Butakhieo, 2020). Many public and private organizations provide the option of working from home as an alternative way to carry out their responsibilities. Compared to working in an office, working from home has both advantages and disadvantages for employees (Carillo et al., 2021). A new policy must create based on practical considerations for the organization and its employees so that working from home can provide new knowledge with flexibility in working hours as a policy in the future to function optimally (Xiao et al., 2021).